2019
DOI: 10.1530/edm-19-0039
|View full text |Cite
|
Sign up to set email alerts
|

Management of primary hyperparathyroidism in pregnancy: a case series

Abstract: Summary Primary hyperparathyroidism (PHPT) is characterised by the overproduction of parathyroid hormone (PTH) due to parathyroid hyperplasia, adenoma or carcinoma and results in hypercalcaemia and a raised or inappropriately normal PTH. Symptoms of hypercalcaemia occur in 20% of patients and include fatigue, nausea, constipation, depression, renal impairment and cardiac arrythmias. In the most severe cases, uraemia, coma or cardiac arrest can result. Primary hyperparathyroidism in pregnancy is rare, with a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 8 publications
0
30
0
2
Order By: Relevance
“…Some studies revealed that patients had an increased chance of miscarriage due to the parathyroid adenoma. [ 6 , 10 , 17 ] In this case, the patient was suffering from threatened abortion, and magnesium sulfate was used to ensure safe gestation. Norman et al reported that patients having an average serum calcium level of 2.9 mmol/L would place them in approximately 70% of miscarriage.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies revealed that patients had an increased chance of miscarriage due to the parathyroid adenoma. [ 6 , 10 , 17 ] In this case, the patient was suffering from threatened abortion, and magnesium sulfate was used to ensure safe gestation. Norman et al reported that patients having an average serum calcium level of 2.9 mmol/L would place them in approximately 70% of miscarriage.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy and safety of treatments in pregnant women are poorly known due to the lack of cases described in the literature [4]. Thus, parathyroidectomy is still considered the best treatment and, as serum calcium levels increase, it becomes increasingly indicated [13]. In the case described, the pregnant woman was not submitted to surgery in the appropriate time because she developed premature amniorrhexis, thus undergoing an emergency cesarean section.…”
Section: Discussionmentioning
confidence: 99%
“…• При наличии абсолютных показаний к хирургическому лечению пациентам с ПГПТ во время беременности рекомендуется проводить паратиреоидэктомию во II триместре [301,[303][304][305][306][307].…”
Section: уур с (удд -4)unclassified